1996
DOI: 10.1136/bmj.312.7028.421
|View full text |Cite
|
Sign up to set email alerts
|

East-West mortality divide and its potential explanations: proposed research agenda

Abstract: There is a sharp divide in mortality between eastern and western Europe, which has largely developed over the past three decades and is caused mainly by chronic diseases in adulthood. The difference in life expectancy at birth between the best and worst European countries in this respect is more than 10 years for both sexes. The reasons for these differences in mortality are not clear and data currently available permit only speculation. The contributions of medical care and pollution are likely to be modest; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
126
0
8

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 320 publications
(139 citation statements)
references
References 20 publications
5
126
0
8
Order By: Relevance
“…Ezzati and Lopez 2004), many studies on the determinants of all-cause mortality differences between countries have looked into the role of smoking, and have found that smoking has had a significant impact (e.g., Bobak and Marmot 1996;Spijker 2003;Janssen, Kunst, and Mackenbach 2007;Staetsky 2009;Preston, Glei, and Wilmoth 2010a;Rostron and Wilmoth 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Ezzati and Lopez 2004), many studies on the determinants of all-cause mortality differences between countries have looked into the role of smoking, and have found that smoking has had a significant impact (e.g., Bobak and Marmot 1996;Spijker 2003;Janssen, Kunst, and Mackenbach 2007;Staetsky 2009;Preston, Glei, and Wilmoth 2010a;Rostron and Wilmoth 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Weltkrieg einen deutlichen Zugewinn an Lebenserwartung aufwiesen und damit den Abstand zum Westen beinahe aufgeholt hatten, öffnete sich die Schere unterschiedlicher Lebenserwartung zwischen West und Ost seit Ende der sechziger Jahre zunehmend. So hat beispielsweise die durchschnittliche Lebenserwartung junger Männer in den letzten 20 Jahren in den meisten westeuropäischen Ländern deutlich zugenommen, während sie in beinahe allen osteuropäischen Ländern zurückgegangen ist [2]. Nach neuen Berechnungen der Weltgesundheitsorganisation existiert hier eine Kluft in der durchschnittlichen Lebenserwartung von mehr als sechs Jahren.…”
Section: Sozial Ungleich Verteilte Sterberisiken: Umfang Und Erklärununclassified
“…Aber auch mangelnde Gewichtskontrolle und Bewegungsarmut, fettreiche und vitaminarme Ernährung sowie unkontrolliert hoher Alkoholkonsum tragen zur schichtspezifischen Exzessmorbidität und -mortalität wesentlich bei, und zwar sowohl zur Erklärung sozialer Differentiale innerhalb von Gesellschaften wie auch im Gefälle zwischen Ostund Westeuropa. So kommen Bobak und Marmot in einer neuen Arbeit zu der Erkenntnis, dass mehr als 50% der Varianz bei der Lebenserwartung von Män-nern und Frauen zwischen ost-und westeuropäischen Ländern auf unangemessenes Ernährungsverhalten, Zigarettenrauchen und Alkoholkonsum zurückge-führt werden können [2]. Darin zeigt sich das gewaltige präventivmedizinische Potential dieser Forschungsbefunde.…”
Section: Sozial Ungleich Verteilte Sterberisiken: Umfang Und Erklärununclassified
See 1 more Smart Citation
“…This paper is therefore concerned with these lifestyle (micro) risk factors. Smoking was regarded a major factor of mortality in CEEC (Bobá k & Marmot, 1996). The central remit of the paper is the understanding the risk factors behind the poor health status of Romanian population.…”
mentioning
confidence: 99%